A mindfulness-based compassion workshop and pre-session preparation to enhance therapist effectiveness in psychotherapy: A pilot study. Issue 3 (3rd July 2022) - Hunt, Carly A.; Goodman, Rachael D.; Hilert, Alexander J.; Hurley, Wilson; Hill, Clara E.
ABSTRACT: We investigated the impact of a 1.5 hr workshop based on mindfulness-based compassion practices (MBCP) for 6 doctoral student therapists, followed by these therapists engaging in pre-session preparation for each of their clients in one of 3 randomly assigned conditions (MBCP, self-supervision, preparation-as-usual) over a 1-month period. State mindfulness and meditation self-efficacy increased following the workshop. Therapist ratings of session effectiveness were higher following pre-session meditation relative to preparation-as-usual, although there were no client-rated differences in session outcome. In a focus group, therapists reported that the workshop was generally helpful, and noted that pre-session MBCP led to a positive state of being and increased self-care. However, they felt rushed to fit in the exercises and some doubted their meditation self-efficacy. They suggested that longer, at-home practice might be more beneficial than pre-session exercises. We encourage replication in larger samples varying the amount and format of meditation training for improving outcomes. Practical Implications Therapist engagement in 2 minutes of meditation immediately prior to sessions may support therapy effectiveness Brief meditation provides an opportunity for therapists to engage in self-care and grow positive inner states Therapists who implement pre-session meditation may encounter challenges, such as tiredness and difficulty fitting in meditation between therapy sessions